Theoretical provisions of programming of strategic development of industry in the conditions of the formation of Industry 5.0 - Glukhov Vladimir; Babkin Aleksandr; Batukova Louisa; Shkarupeta Elena; Makhmudova Guljakhon (π-Economy)
In the context of the ongoing transition to an integrated cyber-information society and the corresponding cyber-information mode of production, the global industry is overcoming a period of deep systemic transformations at the macro-, meso- and micro-levels. The organizational foundations of industry, its financial, investment and information support acquire fundamentally new meanings and forms, which have no analogues in history. Today, in different industries, special mesostructures – umbrella industrial EICSG ecosystems – are emerging and becoming increasingly influential. This is explained by the fact that these mesostructures, together with system-forming industries, are designed to ensure infrastructural and functional basis of Industry 5.0, which is the primary form of the newly emerging cyber-information mode of production. The most important organizational and managerial problem of industry at the present stage of historical evolution remains the unsolved problem of the transition from “manual” management of large industrial mesostructures to organizational programming. The latter is a special organizational mechanism, which removes or significantly alleviates the problem of subjectivity, inconsistency, untimeliness, inadequacy of management decisions in conditions of high organizational and scientific and technological complexity of management facilities, volatility and uncertainty of their external environment, a large number of stakeholders influencing the decision-making processes. Basically, organizational programming is a mechanism for coordinating the objective organizational and institutional dynamics of industry, predetermined by the impact of scientific and technological progress. Organizational programming is functionally focused on identifying and understanding the laws and models of objective development of the industrial sphere and coordinating the integrated mass of joint efforts and resources of society to achieve optimal evolutionary transformations of industry.Solving the problem of transferring the management of industrial mesostructures to the mechanisms of organizational programming is hindered by: at the conceptual level – the lack of well-developed theoretical and methodological foundations of organizational programming of strategic industrial development; at the scientific and practical level – methodological, informational and instrumental inconsistency of research by specialists of different profiles in terms of creating an organizational platform of strategic industrial development program. The article proposes scientific and methodological provisions that form the foundations of organizational programming of strategic industrial development, as well as contribute to the development of methodological, informational and instrumental coherence of research for specialists of different profiles.